Decision Support System for Selecting Cleaning Service Supervisors at the Indragiri Hilir Regent's Office Using the ELECTRE Method - Mohd Fitra Ramadhan; Ilyas (STMIK Methodist Binjai, 2026)
The selection of cleaning service foremen in government institutions is often subjective, leading to inconsistent performance evaluations. This study aims to design and implement a Decision Support System (DSS) using the ELECTRE method to objectively select the best foreman at the Indragiri Hilir Regent's Office. The system employs an outranking mechanism with concordance and discordance index analysis to systematically eliminate candidates failing to meet managerial thresholds. Five evaluation criteria were applied: leadership, discipline, responsibility, loyalty, and communication skills. The results show that the ELECTRE-based DSS successfully identified the most suitable candidate by eliminating alternatives with critical weaknesses, producing transparent and auditable recommendations. This system reduces cognitive bias in decision-making and provides a strategic instrument for improving public service standards within the regional secretariat. The findings confirm that ELECTRE is effective for operational staff selection where minimum competency thresholds are non-negotiable.